A Nano‐sized Supramolecule Beyond the Fullerene Topology1. Issue 49 (6th October 2014) - Dielmann, Fabian; Heindl, Claudia; Hastreiter, Florian; Peresypkina, Eugenia V.; Virovets, Alexander V.; Gschwind, Ruth M.; Scheer, Manfred
Abstract The reaction of [CpBnFe(η5‐P5)] (1) (CpBn=η5‐C5(CH2Ph)5) with CuI selectively yields a novel spherical supramolecule (CH2Cl2)3.4@[(CpBnFeP5)12CuI54(MeCN)1.46] (2) showing a linkage of the scaffold atoms which is beyond the Fullerene topology. Its extended CuI framework reveals an outer diameter of 3.7 nm—a size that has not been reached before using five‐fold symmetric building blocks. Furthermore, 2 shows a remarkable solubility in CH2Cl2, and NMR spectroscopy reveals that the scaffold of the supramolecule remains intact in solution. In addition, a novel 2D polymer [CpBnFe(η5‐P5)2Cu6(μ‐I)2(μ3‐I)4]n (3) with an uncommon structural motif was isolated. Its formation can be avoided by using a large excess of CuI in the reaction with 1.